2009
DOI: 10.1007/s11783-009-0142-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrate concentration on biological hydrogen production by mixed cultures

Abstract: The effects of nitrate on fermentative hydrogen production and soluble metabolites from mixed cultures were investigated by varying nitrate concentrations from 0 to 10 g N/L at 35°C with an initial pH of 7.0. The results showed that the substrate degradation rate, hydrogen production potential, hydrogen yield, and average hydrogen production rate initially increased with increasing nitrate concentrations from 0 to 0.1 g N/L, while they decreased with increasing nitrate concentrations from 0.1 to 10 g N/L. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Hydrogen production from treated sludge in this study obtained VHPR of 13.4–24.6 mL h –1 L –1 , which was higher than VHPR of 0.18–6.59 mL h –1 L –1 obtained in the study using alkaline-treated sludge as the substrate . Various studies have found the positive effect of nutrients, such as minerals, vitamins, and trace elements, on fermentative hydrogen production, concluding that the waste-activated sludge was rich in various nutrients, which can be helpful for fermentative hydrogen production …”
Section: Resultscontrasting
confidence: 59%
“…Hydrogen production from treated sludge in this study obtained VHPR of 13.4–24.6 mL h –1 L –1 , which was higher than VHPR of 0.18–6.59 mL h –1 L –1 obtained in the study using alkaline-treated sludge as the substrate . Various studies have found the positive effect of nutrients, such as minerals, vitamins, and trace elements, on fermentative hydrogen production, concluding that the waste-activated sludge was rich in various nutrients, which can be helpful for fermentative hydrogen production …”
Section: Resultscontrasting
confidence: 59%
“…Besides the carbon sources, nitrogen and phosphorus were also released to the liquid phase, which are necessary elements for microbial metabolism. 43 After sonication, nitrogen was increased from 5.0 to 33.8 mg/L and phosphorus was increased from 22.1 to 44.6 mg/L. A little decrease in pH was observed from 7.7 to 7.2 after the treatment, which may be due to the VFA formation accompanied by carbohydrate reduction in the treatment process.…”
Section: Resultsmentioning
confidence: 91%
“…Besides the carbon sources, nitrogen and phosphorus were also released to the liquid phase, which are necessary elements for microbial metabolism . After sonication, nitrogen was increased from 5.0 to 33.8 mg/L and phosphorus was increased from 22.1 to 44.6 mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…Molybdenum plays a very specific role in the activity of dehydrogenase which contains subunits requiring molybdenum as cofactor to function (Popov and Lamzin, 1994;McDowall et al, 2014). could lead to decreased productivity (Lin and Lay, 2004; ; Wang et al, 2009 ). An appropriate C/N and C/P are fundamental for any biological processes to function metabolically effective.…”
Section: Discussionmentioning
confidence: 99%